2016
DOI: 10.3390/molecules21020200
|View full text |Cite
|
Sign up to set email alerts
|

The Diels-Alder Cycloaddition Reaction of Substituted Hemifullerenes with 1,3-Butadiene: Effect of Electron-Donating and Electron-Withdrawing Substituents

Abstract: Abstract:The Diels-Alder (DA) reaction provides an attractive route to increase the number of six member rings in substituted Polycyclic Aromatic Hydrocarbons (PAHs). The density functional theory (DFT) B3LYP method has been used in this work to inquire if the substitution of H over the edge of triindenetriphenylene (pristine hemifullerene 1) and pentacyclopentacorannulene (pristine hemifullerene 2), could improve the DA cycloaddition reaction with 1,3-butadiene. The substituents tested include electron-donati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Our previous studies of the substituent effect in the reactivity of C 30 H 10 suggested that it is possible to increase its reactivity in the DA reactions. 31,32 The results presented support the possibility to dimerize C 30 H 10 and the existence of C 60 H 20 . In fact, the fullerene hydride C 60 H 20 has been detected in the mass spectra of C 60 hydrides synthesized by condensation of benzene molecules, 49 although, the structure of C 60 H 20 formed in these experiments is not necessarily the belt-like structure discussed here, which is closely connected to the structure of the precursor C 30 H 10 .…”
Section: ) Stepwise Dimerizationsupporting
confidence: 72%
See 1 more Smart Citation
“…Our previous studies of the substituent effect in the reactivity of C 30 H 10 suggested that it is possible to increase its reactivity in the DA reactions. 31,32 The results presented support the possibility to dimerize C 30 H 10 and the existence of C 60 H 20 . In fact, the fullerene hydride C 60 H 20 has been detected in the mass spectra of C 60 hydrides synthesized by condensation of benzene molecules, 49 although, the structure of C 60 H 20 formed in these experiments is not necessarily the belt-like structure discussed here, which is closely connected to the structure of the precursor C 30 H 10 .…”
Section: ) Stepwise Dimerizationsupporting
confidence: 72%
“…30 Although the full C 30 H 10 (1) has not been synthesized yet, one can expect that similar methods will allow for the synthesis of this fragment. On the basis of ab initio calculations Mojica et al 31,32 suggested that C 30 H 10 (1) is a good dienophile towards DA cycloaddition reaction with butadiene and possesses high symmetry, which makes it an ideal fragment to produce C 60 H 20 and the C 60 fullerene (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The definite mechanism for the formation of PAHs is not well understood. Some researchers proposed that they might be formed through free radical reactions, intramolecular addition or the polymerization of small molecules [5,6,7]. In meat products, PAHs are formed during processing at a high temperature, such as by smoking, drying, roasting, and grilling [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In this particular case, the F I G U R E 3 Dimerization reactions between two [1+1] type moieties and between two [2+2] type moieties [122] activation barriers are lower than for the other reactions; what is more, the free energies of the process are negative, in contrast to the positive values for the other processes. Later, the same authors [124] used the B3LYP functional to find out whether the Diels-Alder cycloaddition with 1,3-butadiene can be accelerated by replacement of H at the border of triindenetriphenilene (primary hemifulleren 1) and pentacyclopentacorannulene (primary hemifulleren 2). The tested substituents included electron-donating groups (NH 2 , OMe, OH, Me, i-Pr) and electron-withdrawing ones (F, COOH, CF 3 , CHO, CN, NO 2 ).…”
Section: Bowl-shaped Polyenesmentioning
confidence: 99%